A way of computing the Hilbert series - Haider, A. (Algebra and Discrete Mathematics, 2018)
Let S = K[x1, x2, . . . , xn] be a standard graded K-algebra for any field K. Without using any heavy tools of commutative algebra we compute the Hilbert series of graded S-module S/I, where I is a monomial ideal.